Investigation of 3D-printed chitosan-xanthan gum patches - ALTAN, ERAY; GÜNDÜZ, OĞUZHAN; BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
In this study, using a new polymer combination of Chitosan(CH)/Xanthan Gum(XG) has been exhibited for wound dressing implementation by the 3D-Printing method, which was fabricated due to its biocompatible, biodegradable, improved mechanical strength, low degradation rate, and hydrophilic nature to develop cell-mimicking, cell adhesion, proliferation, and differentiation. Different concentrations of XG were added to the CH solution as 0.25, 0.50, 0.75, 1, and 2 wt% respectively in the formic acid/distilled water (1.5:8.5) solution and rheologically characterized to evaluate their printability. The results demonstrated that high mechanical strength, hydrophilic properties, and slow degradation rate were observed with the presence and increment of XG concentration within the 3D-Printed patches. Moreover, in vitro cell culture research was conducted by seeding NIH 3T3 fibroblast cells on the patches, proving the cell proliferation rate, viability, and adhesion. Finally, 1% XG and 4% CH containing 3D-Printed patches were great potential for wound dressing applications.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Fizikokimya; Polimer Karakterizasyonu; Diğer; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Physical Chemistry; Characterization of Polymers; Other; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); KİMYA, UYGULAMALI; Temel Bilimler (SCI); POLİMER BİLİMİ; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); POLYMER SCIENCE; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Klinik Biyokimya; Kanser Araştırmaları; Moleküler Biyoloji; İlaç Keşfi; Yaşlanma; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Biyokimya; Yapısal Biyoloji; Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Biochemistry; Structural Biology; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences; 3D printing; Biomaterials; Wound dressing; Optimisation; IN-VITRO; HYDROGELS; SCAFFOLDS; FILMS; ACID; FTIR; 3D printing; Biomaterials; Wound dressing; Optimisation